Editor Fatigue: Can Political Science Journals Increase Review Invitation-Acceptance Rates?. Issue 1 (6th January 2022) - Franceschet, Antonio; Lucas, Jack; O'Neill, Brenda; Pando, Elizabeth; Thomas, Melanee
ABSTRACT: In many political science journals, fewer than half of the invitations sent to potential reviewers are accepted. These low acceptance rates increase workloads for editors and lengthen the review process for authors. This article reports analyses of reviewer invitation acceptance at the Canadian Journal of Political Science between 2017 and 2020. We first describe predictors of invitation acceptance using a coded dataset of almost 1, 500 invitations. We find that reviewers who are personally familiar to editors, located in the same country as the journal, and more junior scholars were more likely to accept invitations. We then report the results of an experiment that tested the effect of three letters on invitation acceptance. We find that a short personal note from the editor to accompany the auto-generated system message may increase reviewer acceptance rates but highlighting the journal's prestige or reviewer recognition does not. We conclude by discussing the practical implications of our findings for editorial-team design and the editorial process.